The factors for Limited use of Gastric Emptying Scintigraphy in the Management of Diabetic Gastroparesis - Sanchay, Jain; Vandana, K Dhingra (Journal of Radiation and Nuclear Medicine, 2021)
A practice review discusses factors limiting the use of gastric emptying scintigraphy in diabetic gastroparesis, including protocols, access, and patient preparation, with suggestions to improve utility.